Cezzane - Sanders, Michael , 1950- (Tunbridge Wells : Search Press, 2010)
Learn to paint like the masters in this inspiring series. In this title, Michael Sanders shows how to paint three of Cezanne's masterpieces in acrylics, and two further projects show how to paint in the style of Cezanne. Tracings are provided to eliminate the drawing stage
"Free tracings inside." --Cover
Includes index
Keywords: Cezanne, Paul , -- 1839-1906 -- Criticism and interpretation; Acrylic painting -- Technique